Kekalahan Amerika Sebagai Negara Super Power Pada Saat Perang Vietnam (1954-1975) - Stephani Dania N. P. (Jurnal Ilmiah Hubungan Internasional, 2013)
As we know that the Vietnam War was the greatest war in the history of the United States, because of the war that lasted for 20 years have been eating so many casualties and cause material loss and spiritual huge especially for the United States. The Vietnam War is a terrible war going on throughout history, due to the emergence of a conflict between two ideologies were very influential in the world of liberal democracy to communist Vietnam, resulting in the outbreak of the country into two parts, namely the North Vietnam (communist) and South Vietnam (liberal democracy). Surely split two countries aided by allies such as France, the United States and China, so the cause of tension is prolonged that war spread to Laos and Cambodia. During the war the United States is trying to help South Vietnam in order to avoid the spread of communism in the state, because it is very dangerous for the existence of the United States as the adherents of liberal democracyKeywords : Vietnam War, Communism, Liberalism, United States, existance